Pengetahuan dan Sumber Informasi Anti-Doping di Kalangan Atlet Indonesia: Penguatan Praktik Olahraga Bersih: Anti-doping Knowledge and Information Sources Among Indonesian Athletes: Strengthening Clean Sport - Penggalih, Mirza Hapsari Sakti Titis; Muslichah, Rahadyana; Niamilah, Ibtidau; Solichah, Kurnia Mar'atus; Reswati, Vigur Dinda Yulia; Muarifati, Shafira Husna; Adi, Afifah Laksita (Amerta Nutrition, 2025)
Background: Doping threatens sport and athlete health. Limited knowledge and insufficient access to anti-doping education increase the risk of intentional or unintentional violations. In Indonesia, very few studies have focused on athletes’ understanding of anti-doping regulations and their educational experiences. Objectives: This study aimed to identify the level of anti-doping knowledge and the sources of information that athletes received as a basis for strengthening clean sport practices. Methods: This cross-sectional quantitative study enrolled 149 Indonesian athletes who answered an online standardized questionnaire previously tested for validity and reliability. The instrument encompassed knowledge and educational experiences related to anti-doping. To examine differences in knowledge scores across demographic characteristics, data were analyzed descriptively and by bivariate comparisons. Results: Participants were predominantly 12–17 years old (58.4%), male (65.1%), and represented 18 sports disciplines. Only 36.9% had ever received anti-doping education, and most information was received from coaches. The mean knowledge score was 68.5 (SD=19.9), with 38% classified as having a good knowledge level. Age was the only demographic factor significantly associated with knowledge scores (p-value=0.039). Conclusions: Indonesian athletes generally have moderate anti-doping knowledge, with notable disparities between age groups and weaknesses in specific areas of understanding. Most athletes reported receiving anti-doping information from coaches and the Indonesia Anti-Doping Organization. These findings highlight the need to develop more targeted and experience-based education strategies that actively involve key stakeholders to ensure consistent and standardized delivery of information.